TEAM ORIENTED LEADERSHIP: A NEW APPROACH TO MOTIVATE SALESPERSON - Sri Ayuni; Diah Ayu Kusumawati; Wasitowati Wasitowati (STIE Pelita Nusantara Semarang, 2023)
This study examines how to achieve sales performance through team oriented leadership and team work quality. Teamwork can run smoothly if in organization have a team-oriented leader. The sampling technique used snowball sampling with the selection of respondents using purposive sampling (non probability sampling). This study used a sample of 348 salespeople from the life insurance industry. The data was collected by distributing questionnaires and direct interviews with salespeople. The results showed that team-oriented leadership and teamwork can improve sales performance. Good and strong quality of teamwork can be achieved through team-oriented leadership. So that these two variables can jointly achieve the best performance in sales activities.